Phase vapor–liquid equilibrium for the solutions of dimethylzinc and dimethyl selenide - Герасимчук, С. І.; Полюжин, І. П.; Мельник, Г. В.; Павловський, Ю. П.; Сергеєв, В. В.; Gerasymchuk, S. I.; Poliuzhyn, I. P.; Melnyk, H. V.; Pavlovskyi, Yu. P.; Sergeyev, V. V. (Lviv Politechnic Publishing House, 2019)
Розглянуто парорідинну рівновагу розчину диметилцинк-диметилселен. Для опису цієї рівноваги запропоновано модель Вільсона. Використано дані щодо температурної залежності тиску насиченої пари високочистих зразків диметилцинку, диметилселену та їх еквімолекулярного розчину, отриманих тензиметричним методом. Застосовуючи математичний пакет програм Mathсad 14, методом ітерацій розраховано параметри моделі Вільсона. На основі цих параметрів пораховано коефіцієнти активності компонентів розчину, надлишкові функції розчину: HE, GE, “зв’язана енергія” TSE. Побудовано ізотермічні Р-Х діаграми стану системи диметилцинк-диметилселен. За результатами розрахунків зроблено висновки: про від’ємне відхилення даної системи від закону Рауля та про гомогенність розчину в усьому інтервалі концентрацій та температур (280–340 К).

The paper is devoted to the vapor-liquid equilibrium for solution of dimethylzincdimethylselenide. For the description of this equilibriumWilson’s model is proposed. We used data obtained by the tensometric method on the temperature dependence of the saturated vapor pressure for high-purity samples of dimethylzinc, dimethyl selenide and their equimolecular solution. Using the mathematical program package MathCAD 14, the Wilson’s model parameters were calculated by the iterative method. On basis of these parameters calculation were provided for the activity coefficients of the solution components, the excess functions of the solution: HE, GE, and the “bound energy” as TSE. Isothermal P-X diagrams of the state were graphed for the dimethylzinc dimethylselenide system. From these calculations, the following conclusions were made: about the negative deviation of this system from the Raoult’s law and about the homogeneity of the solution within the range of all concentrations and temperatures (280–340 K).
Фазова рівновага пара–рідина розчинів диметилцинку та диметилселену
Keywords: диметилцинк; диметилселен; розчин; тиск насиченої пари; діаграма стану; коефіцієнти активності; азеотроп; надлишкові функції змішування; dimethylzinc; dimethyl selenide; solution; saturated vapor pressure; diagram of the state; activity coefficients; azeotrope; excess functions of mixing